Determination of ochratoxin A in maize bread samples by LC with fluorescence detection - Juan, C. (2007)
Ochratoxin A (OTA) is a secondary fungal metabolite produced by several moulds, mainly by Aspergillus ochraceus, A. carbonarius, A. niger and by Penicillium verrucosum. The present work shows the results of comparative studies using different procedures for the analysis of OTA in maize bread samples. The studied analytical methods involved extraction with different volumes of PBS/methanol, different extraction apparatus, and clean-up through immunoaffinity columns. The separation and identification were carried out by high-performance liquid chromatography with fluorescence detection. The optimized method for analysis of OTA in maize bread involved extraction with PBS:methanol (50:50), and clean-up with IAC column. The limit of quantification was 0.033 ng g-1. Recoveries ranged from 87% to 102% for fortifications at 2.000 and 0.500 ng g-1, respectively, within-day R.S.D. of 1.4% and 4.7%. The proposed method was applied to 15 samples and the presence of OTA was found in nine samples at concentrations ranging from nd to 2.650 ng g-1.